Spray volume deposits and fungicide efficacy on soybean rust (Phakopsora pachyrhizi) - Prado, Evandro Pereira [UNESP]; Raetano, Carlos Gilberto [UNESP]; Dal Pogetto, Mario Henrique Ferreira do Amaral [UNESP]; Christovam, Rafael de Souza [UNESP]; Lopes, Paulo Renato Matos [UNESP]; Tomaz, Rafael Simões [UNESP]; Ferreira-Filho, Pedro José; Zied, Diego Cunha [UNESP]; Guerreiro, Julio Cesar; de Cerqueira, Denise Tourino Rezende [UNESP] (Southern Cross Publishing, 2019)
Soybean rust (SBR), caused by Phakopsora pachyrhizi, is one of the most destructive fungal diseases affecting soybean yields in many countries. Fungicide application methods that provide better SBR control efficacy may reduce soybean losses due to this disease. We investigated the effects of spray volumes applying the fungicide pyraclostrobin plus epoxiconazol at 133 + 50 g a.i. ha-1 by a conventional sprayer (CS) and an air-assisted sprayer (AAS). Field experiments were conducted comparing the effects of spray volumes of 110, 160, and 210 L ha-1 and two application techniques (CS and AAS) on spray deposits and SBR control. Fungicide efficacies were measured by disease severity, thousand seed weight, and yield. Correlations between disease severity and yield were also assessed. All treatments were applied with an Advance 2000 AM18 sprayer. In general, SBR disease and yield did not differ significantly when fungicide applications were applied with AAS compared to CS. Increasing the spray volume from 110 to 210 L ha-1 did not increase spray deposit coverage on soybean leaves. Low disease severity was obtained by fungicide applications using a spray volume of 210 L ha-1. Safe recommendations of ground spray volumes for SBR control should be between 160 and 210 L ha-1, using hydraulic nozzles.
Keywords: Glycine max; Pesticide application technology; Spray deposits; Spray rate